Clinicopathological Profile of 66 Patients with Carcinoma Stomach in North-East Part of Bangladesh (Journal of Enam Medical College, 2019)
Background: There is wide variation in the prevalence of carcinoma stomach throughout the world. In some parts of the world it is decreasing whereas in the other parts it is increasing. Also there are variations in the risk factors of the disease.Objective: To see clinicopathological profile of patients of carcinoma stomach in North-East part of Bangladesh.Materials and Methods: Consecutive new patient diagnosed as carcinoma of stomach were interviewed and data was recorded in a data sheet.Results: Total 66 cases, age varying from 26−77 (mean 52) years, male 45 (68.2%) and female 21 (31.8%) were enrolled. Out of them 44 (66.7%) were above 45 years. People from lower economic group (51, 78.8%) and rural area (39, 59.1%) were predominantly affected. Commonest presenting symptoms were weight loss, abdominal pain and vomiting. Common site of lesion was antrum and common histopathological type was adenocarcinoma (64, 97%).Conclusion: Carcinoma stomach is a disease of older age group and male are predominantly affected. Smoking, tobacco and betel nut chewing are risk factors. Lower income group and rural people are more affected.J Enam Med Col 2019; 9(3): 166-169